2018
DOI: 10.1242/jeb.169425
|View full text |Cite
|
Sign up to set email alerts
|

Insights into brown adipose tissue evolution and function from non-model organisms

Abstract: Brown adipose tissue (BAT) enables adaptive thermoregulation through heat production that is catalyzed by mitochondrial uncoupling protein 1 (UCP1). BAT is frequently studied in rodent model organisms, and recently in adult humans to treat metabolic diseases. However, complementary studies of many non-model species, which have diversified to many more ecological niches, may significantly broaden our understanding of BAT regulation and its physiological roles. This Review highlights the research on non-model or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 90 publications
(97 reference statements)
0
26
0
1
Order By: Relevance
“…UCP1 gene was inactivated in numerous placental mammal clades (e.g. horses, whales, elephants, sea cows, hyraxes, sloths) and a number of these groups have species that are extremely cold tolerant, suggesting the existence of alternate NST mechanisms [111,112]. The whole swine family lost the UCP1 protein due to disruptions in the gene about 20 Ma [113].…”
Section: (B) Sarcolipin-based Thermogenesis In Mammals Lacking Brown mentioning
confidence: 99%
“…UCP1 gene was inactivated in numerous placental mammal clades (e.g. horses, whales, elephants, sea cows, hyraxes, sloths) and a number of these groups have species that are extremely cold tolerant, suggesting the existence of alternate NST mechanisms [111,112]. The whole swine family lost the UCP1 protein due to disruptions in the gene about 20 Ma [113].…”
Section: (B) Sarcolipin-based Thermogenesis In Mammals Lacking Brown mentioning
confidence: 99%
“…The expression of UCP1 causes a proton leak in the mitochondrial respiratory chain leading to energy dissipation as heat rather than in the form of adenosine triphosphate (ATP), therefore; it is mainly associated with energy expenditure and metabolism. 9 Other key proteins associated with brown fat phenotype include; cell-deathinducing DNA fragment factor 45-like effector A (CIDEA) and elongation of very long fatty acids 3 (ELOVL3). 10,11 The main biological function of CIDEA has not been fully defined but has been mainly implicated in lipid and energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, treatment with 25 µM GN up-regulated mRNA levels of FAO genes, such as peroxisome proliferator-activated receptor alpha (Pparα), peroxisome proliferator-activated receptor delta (Pparδ), carnitine palmitoyltransferase 1 (Cpt1) and carnitine palmitoyltransferase 2 (Cpt2). A recent study suggested that UCP1 in mitochondria inner membranes plays an important role in energy consumption [30,31]. We analyzed differentiated cells treated with GN using immunostaining.…”
Section: Gn Enhances Thermogenic and Fao Markers In 3t3-l1 Cellsmentioning
confidence: 99%